Electronic Cigarettes and Vaping: A New Challenge in Clinical Medicine and Public Health. A Literature Review - Palazzolo, Dominic L. (Frontiers in Public Health, 2013)
Electronic cigarette (e-cigarette) use, or vaping, in the United States and worldwide is increasing. Their use is highly controversial from scientific, political, financial, psychological, and sociological ideologies. Given the controversial nature of e-cigarettes and vaping, how should medical care providers advise their patients? To effectively face this new challenge, health care professionals need to become more familiar with the existing literature concerning e-cigarettes and vaping, especially the scientific literature. Thus, the aim of this article is to present a review of the scientific evidence-based primary literature concerning electronic cigarettes and vaping. A search of the most current literature using the pubmed database dating back to 2008, and using electronic cigarette(s) or e-cigarette(s) as key words, yielded a total of 66 highly relevant articles. These articles primarily deal with (1) consumer-based surveys regarding personal views on vaping, (2) chemical analysis of e-cigarette cartridges, solutions, and mist, (3) nicotine content, delivery, and pharmacokinetics, and (4) clinical and physiological studies investigating the effects of acute vaping. When compared to the effects of smoking, the scant available literature suggests that vaping could be a “harm reduction” alternative to smoking and a possible means for smoking cessation, at least to the same degree as other Food and Drug Administration-approved nicotine replacement therapies. However, it is unclear if vaping e-cigarettes will reduce or increase nicotine addiction. It is obvious that more rigorous investigations of the acute and long-term health effects of vaping are required to establish the safety and efficacy of these devices; especially parallel experiments comparing the cardiopulmonary effects of vaping to smoking. Only then will the medical community be able to adequately meet the new challenge e-cigarettes and vaping present to clinical medicine and public health.